The novel cis-encoded antisense RNA AsrC positively regulates the expression of rpoE-rseABC operon and thus enhances the motility of Salmonella enterica serovar typhi - Zhang, Qi; Zhang, Ying; Zhang, Xiaolei; Zhan, Lifang; Zhao, Xin; Xu, Shungao; Sheng, Xiumei; Huang, Xinxiang (Frontiers in Microbiology, 2015)
Bacterial noncoding RNAs are essential in many cellular processes, including response to environmental stress, and virulence. Deep sequencing analysis of the Salmonella enterica serovar Typhi (S. Typhi) transcriptome revealed a novel antisense RNA transcribed in cis on the strand complementary to rseC, an activator gene of sigma factor RpoE. In this study, expression of this antisense RNA was confirmed in S. Typhi by Northern hybridization. Rapid amplification of cDNA ends and sequence analysis identified an 893 bp sequence from the antisense RNA coding region that covered all of the rseC coding region in the reverse direction of transcription. This sequence of RNA was named as AsrC. After overexpression of AsrC with recombinantant plasmid in S. Typhi, the bacterial motility was increased obviously. To explore the mechanism of AsrC function, regulation of rseC and rpoE expression by AsrC was investigated. We found that AsrC increased the levels of rseC mRNA and protein. The expression of rpoE was also increased in S. Typhi after overexpression of AsrC, which was dependent on rseC. Thus, we propose that AsrC increased RseC level and indirectly activating RpoE which can initiate fliA expression and promote the motility of S. Typhi.